Management of dystocia complicated by fetal ascites in a Holstein Friesian cow - Wasef, Al; Mohanta, Uday Kumar; Hossan, Md Farhad; Islam, Md. Rashedul; Hossain, Hafsa (Universitas Airlangga, 2025)
A five-and-a-half-year-old crossbred Holstein Friesian cow was presented with a history of prolonged second-stage labor. According to the owner, the first water bag had appeared approximately seven hours prior to reporting to the Upazila Veterinary Hospital in Manoharganj, Cumilla, Bangladesh. Upon on-farm examination, a per-vaginal assessment revealed that the fetus was in a posterior presentation, and the fetal abdomen was markedly distended with fluid, giving it a characteristic